Pelatihan Cara Penyajian Makanan yang Baik dalam Upaya Peningkatan Kinerja Pemasaran Produk UMKM Warung Nasi Kota Bogor - Sesar Husen Santosa; Heryudianto Vibowo; Agung Prayudha Hidayat; Ridwan Siskandar; Khoirul Aziz Husyairi; Bayu Suriaatmaja Suwanda; Annisa Rizkiriani (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Rice stalls are one of the Small and Medium Enterprises (SMEs) that have significantly contributed to efforts to improve the economy. This community service activity aims to increase the ability of SME rice stalls in Bogor to manage Good Food Production Methods (CPMB) to improve marketing performance. The results of the pre-test and post-test identification revealed three potential rice stalls. The evaluation results for the training activities showed that there were three possible rice stalls with the highest post-test results, namely the Pa de Umar rice stall (score 80.00), Kabita (score 73.33), and Selamat (score 70.00). Based on the three rice stalls above, selecting potential rice stalls for mentoring activities was carried out using the Bayes method, and the Pa de Umar Rice Stall was chosen with an alternative value of 4.40. Implementing the CPMB training is expected to increase the understanding and knowledge of Bogor City rice stall participants so that business actors can improve business performance and profits.